2017
DOI: 10.3126/kumj.v13i4.16836
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Critical Knowledge on Maternal and Newborn care Services among Primary Level Nurse Mid-wives in Kapilvastu District of Nepal

Abstract: BackgroundDespite greater emphasis on maternal and neonatal health through policy and programming in Nepal, maternal and neonatal health is still not impressive. Health care providers' knowledge assessment on maternal and neonatal care has been well documented elsewhere, but it is very little understood in Nepal. ObjectiveThe primary objective of this study was to assess the critical knowledge of primary level nurse-midwives on maternal and newborn care in Kapilvastu District of Nepal. MethodThis was an Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A study in Yemen reported that formal HCPs scored only 17.2% on questions related to maternal‐newborn care counselling (Ba Saleem et al ). In Nepal, 69% of nurse‐midwives studied reported poor knowledge levels regarding newborn care (Acharya & Paudel ). Similar findings are reported in Indonesia where declines in neonatal mortality have stalled (Sethi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Yemen reported that formal HCPs scored only 17.2% on questions related to maternal‐newborn care counselling (Ba Saleem et al ). In Nepal, 69% of nurse‐midwives studied reported poor knowledge levels regarding newborn care (Acharya & Paudel ). Similar findings are reported in Indonesia where declines in neonatal mortality have stalled (Sethi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, training related to evidence-based practices is rarely provided to Nepalese nurses [ 14 ]. These might be the contributing factors responsible for incompetencies in some areas of nursing services, if not all [ 15 18 ]. Additionally, commercialization of the profession is strongly attributed to deteriorating nursing education and practice in Nepal [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Competent nurse-midwife practitioner and skilled delivery care are crucial to ensure quality health services for saving of mothers and newborns lives. However, nurse-midwife's knowledge is essential for improving the newborn health; there has been a great gap in recommended knowledge of maternity health services among them in developing countries (7) . The reason of neonatal death was the low levels of knowledge among health workers regarding newborn care (8) .…”
Section: Introductionmentioning
confidence: 99%